Toxicological evaluation of a fruit and vegetable rinse using duck embryo - Macavinta, Uri S.; Dumelod, Benelyn Domingo (1999)
In response to the widespread public suspicion and queries about the safety of the new fruit and vegetable rinse from Procter and Gamble, the toxicological evaluation of the said product using duck embryos was investigated. A total of 240 duck embryos were used as experimental subjects with the aim of determining the relative toxicity of the fruit and vegetable rinse to ordinary tap water. Results show that the fruit and vegetable rinse had the highest mortality relative to the other treatments (i.e. tap water, punctured, uninoculated). The incidence of the toxic effect due to the fruit and vegetable rinse was significant according to the literature values given by the National Research Council. Care should be taken in the usage of the product as it may be detrimental to health. It is recommended that the treated fruits and vegetables should be washed with clean water before eating or further processing.
Thesis (BSFT)--University of the Philippines Diliman
Keywords: Fruit and vegetable rinse; FIT